Portfolios of the rich - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2000)
Recent research has shown that 'rich' households save at much higher rates than others (see Carroll (2000); Dynan Skinner and Zeldes (1996); Gentry and Hubbard (1998); Huggett (1996); Quadrini (1999)) This paper documents another large difference between the rich and the rest of the population: portfolios of the rich are heavily skewed toward risky assets particularly investments in their own privately held businesses The paper explores three possible explanations of these facts First perhaps there is exogenous variation in risk tolerance so that highly risk tolerant households engage in high-risk high-return activities and the risk-lovers who are lucky constitute the rich A second possibility is that capital market imperfections a la Gentry and Hubbard (1998) and Quadrini (1999) require entrepreneurial activities to be largely self-financed and these same imperfections imply that entreprenurial investment will yield high average returns The final possibility is that wealth enters households' utility functions directly as a luxury good as in Carroll (2000) (one interpretation is that this reflects the utility of anticipated bequests) implying that risk aversion declines as wealth rises The paper concludes that the overall pattern of facts suggests both Carroll-style utility and Gentry/Hubbard-Quadrini style capital market imperfections are important.
Keywords: D10; D31; D91; E21; G11; 330; portfolios; risk aversion; entrepreneurship; capital market imperfections; bequests; Kapitalanlage; Investitionsrisiko; Portfolio-Management; Privater Haushalt; USA